2017
DOI: 10.1177/0738894217724135
|View full text |Cite
|
Sign up to set email alerts
|

Lasting peace or temporary calm? Rebel group decapitation and civil war outcomes

Abstract: Existing research has found that killing or capturing rebel group leaders can lead to the termination of civil wars. This paper considers the quality of those terminations, examining how wars end and whether this produces a lasting peace or only a temporary reprieve from violence. Decapitation is expected to weaken rebel groups, shifting the balance of power to the government; however, results suggest that killing or capturing a rebel group leader tends to produce termination through inactivity rather than out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 50 publications
1
3
0
Order By: Relevance
“…Although, after the death of its leader, Abdel Qader Saleh, Liwa al-Tawhid declined to the point where there are conflicting reports about whether it is still operating independently ("Mapping Militant Organizations" 2021). More generally, I find that leadership targeting reduces the frequency and intensity of armed group violence over time, in line with Johnston (2012) and Ryckman (2020). This paper also provides evidence that there are noticeable differences between successfully targeting rebel leaders and assassinating other senior rebel officials, a unique finding in the leadership targeting literature.…”
Section: Resultssupporting
confidence: 66%
“…Although, after the death of its leader, Abdel Qader Saleh, Liwa al-Tawhid declined to the point where there are conflicting reports about whether it is still operating independently ("Mapping Militant Organizations" 2021). More generally, I find that leadership targeting reduces the frequency and intensity of armed group violence over time, in line with Johnston (2012) and Ryckman (2020). This paper also provides evidence that there are noticeable differences between successfully targeting rebel leaders and assassinating other senior rebel officials, a unique finding in the leadership targeting literature.…”
Section: Resultssupporting
confidence: 66%
“…Yet, there are many circumstances when the collapse of a social system would benefit society, including the disruption of terrorist, rebel, and organized crime groups. Previous research has found that terrorist organizations are similarly resilient against exogenous shocks (Carley, Reminga and Kamneva, 2003;Carley, 2006;Moon and Carley, 2007;Price, 2012;Mannes, 2008;Milton and Price, 2020;Ryckman, 2020). This is due in part to these groups' network structure.…”
Section: Introductionmentioning
confidence: 91%
“…Yet, there are many circumstances when the collapse of a social system would benefit society, including the disruption of terrorist, rebel, and organized crime groups. Previous research has found that terrorist organizations are similarly resilient against exogenous shocks (Carley, Reminga and Kamneva, 2003;Carley, 2006;Moon and Carley, 2007;Price, 2012;Mannes, 2008;Milton and Price, 2020;Ryckman, 2020). This is due in part to these groups' network structure.…”
Section: Introductionmentioning
confidence: 92%